2019
DOI: 10.1002/lt.25390
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Benefit and Potential Harm of Induction Therapy in Simultaneous Liver‐Kidney Transplants

Abstract: United States for 2002-2016. The cohort was divided into 3 groups on the basis of induction type: rabbit antithymocyte globulin (r-ATG; n = 831), interleukin 2 receptor antagonist (IL2RA; n = 1558), and no induction (n = 2333). Primary outcomes were posttransplant all-cause mortality and acute rejection rates in kidney and liver allografts at 12 months. Survival rates were analyzed by the Kaplan-Meier method. A propensity score analysis was used to control potential selection bias. Multivariate inverse probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 52 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…We are surprised by these results mainly for 2 reasons: Our program recently published a series of CLKTs where r‐ATG induction was used in all recipients with excellent outcomes Our program also contributed ~18% (146/831 CLKTs) of the r‐ATG induction group mentioned previously …”
mentioning
confidence: 98%
See 3 more Smart Citations
“…We are surprised by these results mainly for 2 reasons: Our program recently published a series of CLKTs where r‐ATG induction was used in all recipients with excellent outcomes Our program also contributed ~18% (146/831 CLKTs) of the r‐ATG induction group mentioned previously …”
mentioning
confidence: 98%
“…B). It is also interesting to note that AbdulRahim et al reported no difference in the causes of death between the 3 groups . Therefore, it is unclear where the true negative impact of r‐ATG induction lies if the cause of death is not infectious or cardiovascular in nature, which would be expected if this were the case.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Our group recently published Organ Procurement and Transplantation Network registry data comparing outcomes among induction agents in simultaneous liver‐kidney transplantations (SLKTs) in the context of contemporary maintenance immunosuppression of tacrolimus (TAC)/mycophenolic acid (MPA). We primarily looked at posttransplant all‐cause mortality and acute rejection rates in kidney and liver allografts at 12 months in SLKT . We thank Ekser et al for sharing their experience with thymoglobulin as an induction therapy in their population of SLKT patients.…”
mentioning
confidence: 99%